Data communication for drone-enabled internet of things - Yousra Abdul Alsahib S. Aldeen; Haider Mohammed Abdulhadi (Institute of Advanced Engineering and Science, 2021)
Internet of things (IoT) is one of the prominent emerged technology of interconnected devices for people convenient and smart services. Recent advancement in this area caused various new challenges especially deployment of infrastructure. In order to fulfill the network requirements, the dynamic and dedicated drone networks have designed as a cost effective and flexible solution. The technologies of IoT and drone are emerged to collect, forward the data for further process. Data communication among drones and IoT infrastructure is new area of research where various different existing protocol are used. However, still this area need attention due to mobility of drones, obstacles and interferences in these networks. This paper proposes a Drone enabled Data Communication for Internet of Things (DDC-IoT) as a data communication solution for IoT networks, data collection centers and drones. The proposed data commination solution is tested in simulation to analyze its performance especially for real time critical applications in terms of data throughput and data delay.